Urzeczywistnianie się Kościoła w środowisku akademickim na przykładzie ośrodka DA Graniczna w Katowicach - Biela, Bogdan (Studia Pastoralne, 2026)
Academic pastoral ministry in Poland in its history executed various models and concepts and the resulting forms of activity. Currently the ministry faces new challenges due to skyrocketing civilisation transformation. Each academic pastoral ministry centre with its own characteristic features resulting from various conditions executes its own objectives. They must, however, result from basic objectives of academic pastoral ministry and at the same time be open for challenges of the contemporary world. Graniczna Academic Pastoral Ministry Centre at the Assumption of the Blessed Virgin Mary in Katowice executed its objectives on the basis of the ecclesiology of communion and the resulting pastoral strategy plan. The article presents the concept and the forms as well as the methods operation implemented in the centre in 1991–2001. Many of the actions bore specific fruits, therefore in the era of the new evangelisation and calling for “the pastoral ministry of reformation” it is worthwhile to get acquainted with the concept and operations of this academic centre.